Investigating LED lighting spectra to improve plant growth and energy use efficiency - Jiang, Nanjun (2021)
The climate change, natural resource collapsing, the world population increase, and accompanied by the urbanization movements, are forging the global food security issue. Vertical farming as an agriculture mode in the urban areas is designed to meet the city food requirement as a priority, at the same time, the emergence of LED semiconductor light source not only provides an ideal controllable light source for plant cultivation, also offers a mythology for plant photobiology study. It qualified the LED light to be the option meeting the overall requirements for modern agricultural production mode, such as high efficiency, high yield, top quality, ecology and safety, which consequently engaged this lighting method with extensive application prospects.